Creation’s Poetics and Musical Foundation in Antonio Gamoneda’s Voice from his “mudanza” of The Flower Songs of Nezahualcoyotl (2022)
In 2016 Antonio Gamoneda published his translations (“mudanzas”) of some of the poems written by the king-poet Nezahualcoyotl. This paper links Gamoneda's translation experience with one of reanimation of the word. The poet, as a shaman, gives the language its energy back. In other words, he revives it as if it were a living being. This exercise suggests a re-awakening of the melodic properties of the voice as a first step carried out by the translator before reaching the final form of the words. The structure of the following pages will be given by key aspects/terms as cultic function, pharmakon, the nature of the poet or the dialectics between two different models of language.